2009
DOI: 10.1016/j.gca.2009.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Origins of magnetite nanocrystals in Martian meteorite ALH84001

Abstract: The Martian meteorite ALH84001 preserves evidence of interaction with aqueous fluids while on Mars in the form of microscopic carbonate disks. These carbonate disks are believed to have precipitated 3.9 Ga ago at beginning of the Noachian epoch on Mars during which both the oldest extant Martian surfaces were formed, and perhaps the earliest global oceans. Intimately associated within and throughout these carbonate disks are nanocrystal magnetites (Fe 3 O 4 ) with unusual chemical and physical properties, whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 70 publications
(134 reference statements)
9
108
0
1
Order By: Relevance
“…Although not without controversy, it was suggested that low concentrations in minor elements observed in magnetite from Martian meteorite ALH84001 could indicate a biological origin for magnetite (18). This interpretation was supported by abiotic formation of magnetite in the laboratory, leading to high levels of elements other than iron in the crystal products (19,20), except if initial materials highly depleted in doping elements were used (21). However, the degree of magnetite chemical purity in these previous studies was estimated by energy dispersive x-ray spectroscopy (EDXS) coupled with transmission electron microscopy, which is usually limited to the quantification of relatively elevated elemental concentrations, typically higher than 0.1-1% (22).…”
mentioning
confidence: 99%
“…Although not without controversy, it was suggested that low concentrations in minor elements observed in magnetite from Martian meteorite ALH84001 could indicate a biological origin for magnetite (18). This interpretation was supported by abiotic formation of magnetite in the laboratory, leading to high levels of elements other than iron in the crystal products (19,20), except if initial materials highly depleted in doping elements were used (21). However, the degree of magnetite chemical purity in these previous studies was estimated by energy dispersive x-ray spectroscopy (EDXS) coupled with transmission electron microscopy, which is usually limited to the quantification of relatively elevated elemental concentrations, typically higher than 0.1-1% (22).…”
mentioning
confidence: 99%
“…The problem persists, however, since other inorganic techniques, as About magnetite crystals within ALH84001, they probably depict a complex history. Thermal decomposition, that has been claimed for many authors as a possible mechanism to explain the occurrence of magnetite crystals in ALH84001 (Golden et al, 2001;Barber & Scott, 2002;Brearly, 2003;Golden et al, 2004), has been discarded by Thomas-Keprta et al, (2009) andJiménez-López et al, (2012) who have proven that magnetite crystals in ALH84001 are allochthonous, meaning that those crystals were not originated within the carbonate globules that fills the meteorite fractures in which magnetite is embedded. Instead, those crystals might have been washed away from different external sources maybe by the action of water that is assumed to be present in huge quantities in early Mars (Carter et al, 2015) and deposited within the meteorite fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Vuong et al, (2015) have reported high quality magnetite with a high saturation magnetization for particles produced by thermal decomposition. Although along those experiments crystals that meet the biogenicity criteria have been produced, Jiménez-López et al, (2012) 52 from their carbonate precursor that has not been observed in ALH84001, backing the proposition of Thomas-Keprta et al, (2009), that the majority of magnetite crystals found in ALH84001 are allochthonous. Regarding the sets of magnetite crystals synthetised in different MPMS experiments with different proteins, SD size particles with a better trend to crystallographic perfection have been consistently obtained (Amemiya et al, 2007;Prozorov et al, 2007;Rawlings et al, 2014;Valverde-Tercedor et al, 2015).…”
Section: Mpms and Alh84001 Magnetite Comparisonmentioning
confidence: 97%
“…But the original group announcing the discovery continued to investigate all possibilities. Recently they have published a paper, which concluded that the 'magnetic bacteria' features found in the meteorite were not formed by some non-biological thermal event [11].…”
Section: (A) Alh84001 Meteoritementioning
confidence: 99%